2022
DOI: 10.3389/fmicb.2022.928551
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas oryzae Pv. oryzicola Response Regulator VemR Is Co-opted by the Sensor Kinase CheA for Phosphorylation of Multiple Pathogenicity-Related Targets

Abstract: Two-component systems (TCSs) (cognate sensor histidine kinase/response regulator pair, HK/RR) play a crucial role in bacterial adaptation, survival, and productive colonization. An atypical orphan single-domain RR VemR was characterized by the non-vascular pathogen Xanthomonas oryzae pv. oryzicola (Xoc) is known to cause bacterial leaf streak (BLS) disease in rice. Xoc growth and pathogenicity in rice, motility, biosynthesis of extracellular polysaccharide (EPS), and the ability to trigger HR in non-host tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In Xcc , HpaS is a membrane-bound histidine kinase sensor that forms a two-component signal transduction system with HrpG and activates HrpG activity by phosphorylation [ 38 ]. In the Xoc RS105 strain, there is a cross-talk between CheA/VemR and HpaS/HrpG-mediated signaling events that coordinate the hrp gene expression [ 39 ]. In addition to HrpG, regulatory factors have been identified in other Xanthomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…In Xcc , HpaS is a membrane-bound histidine kinase sensor that forms a two-component signal transduction system with HrpG and activates HrpG activity by phosphorylation [ 38 ]. In the Xoc RS105 strain, there is a cross-talk between CheA/VemR and HpaS/HrpG-mediated signaling events that coordinate the hrp gene expression [ 39 ]. In addition to HrpG, regulatory factors have been identified in other Xanthomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…HpaR1 regulates hrp gene expression via hrpG negatively in standard media but positively in plant tissues (An et al, 2011 ). Recently, Zhang et al ( 2020 ) found by ChIP‐seq that in Xcc HrpG could bind to the vemR promoter region in vivo and Cai et al ( 2022 ) showed that in X. oryzae pv. oryzicola the transcription of vemR is repressed by HrpG in nutrient‐rich conditions.…”
Section: Discussionmentioning
confidence: 99%
“…citri and the rice bacterial leaf streak agent Xanthomonas oryzae pv. oryzicola also resulted in a reduction of EPS, motility, virulence, and HR (Cai et al, 2022; Wu et al, 2019). It is possible that the VemR proteins among Xanthomonas species have similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…More down-regulated genes function in flagellar assembly (ko02040), bacterial chemotaxis (ko02030) in cellular process, starch and sucrose metabolism (ko00500), and oxidative phosphorylation (ko00190) indicating that B. velezensis 504 CFSs suppress phenotypes associated with chemotaxis, and motility of Xoc RS105, both of which are related to virulence toward host colonization. Genes involved in bacterial chemotaxis ( flhA , flhB , flgC , flgK , flgL , fliC genes and cheA , cheB , cheD ) were downregulated to suppress bacterial flagellar synthesis and chemotactic motility, reducing bacterial pathogenicity ( Cai et al., 2022 ). Down-regulated expression of nineteen genes in the starch and sucrose metabolism pathway could lead to inadequate intracellular energy supply to bacteria, thus affecting normal bacterial growth.…”
Section: Discussionmentioning
confidence: 99%